Exploring Tactile Perceptual Dimensions Using Materials Associated with Sensory Vocabulary - Sakamoto, Maki; Watanabe, Junji (Frontiers in Psychology, 2017)
Considering tactile sensation when designing products is important because the decision to purchase often depends on how products feel. Numerous psychophysical studies have attempted to identify important factors that describe tactile perceptions. However, the numbers and types of major tactile dimensions reported in previous studies have varied because of differences in materials used across experiments. To obtain a more complete picture of perceptual space with regard to touch, our study focuses on using vocabulary that expresses tactile sensations as a guiding principle for collecting material samples because these types of words are expected to cover all the basic categories within tactile perceptual space. We collected 120 materials based on a variety of Japanese sound-symbolic words for tactile sensations, and used the materials to examine tactile perceptual dimensions and their associations with affective evaluations. Analysis revealed six major dimensions: “Affective evaluation and Friction,” “Compliance,” “Surface,” “Volume,” “Temperature,” and “Naturalness.” These dimensions include four factors that previous studies have regarded as fundamental, as well as two new factors: “Volume” and the “Naturalness”. Additionally, we showed that “Affective evaluation” is more closely related to the “Friction” component (slipperiness and dryness) than to other tactile perceptual features. Our study demonstrates that using vocabulary could be an effective method for selecting material samples to explore tactile perceptual space.